Maladaptive coping strategies and glaucoma progression. Issue 35 (August 2016) - Freeman, Ellen E.; Lesk, Mark R.; Harasymowycz, Paul; Desjardins, Daniel; Flores, Veronica; Kamga, Hortence; Li, Gisèle
Abstract : Abstract: The identification of modifiable risk factors for glaucoma progression is needed. Our objective was to determine whether maladaptive coping styles are associated with recent glaucoma progression or worse visual field mean deviation. A hospital-based case–control study was conducted in the Glaucoma Service of Maisonneuve-Rosemont Hospital in Montreal, Canada. Patients with primary open angle glaucoma or normal tension glaucoma with ≥4 years of follow-up and ≥5 Humphrey visual fields were included. Cases had recent visual field progression as defined according to the Early Manifest Glaucoma Trial pattern change probability maps. Controls had stable visual fields. The Brief Cope questionnaire, a 28-item questionnaire about 14 different ways of coping with the stress of a chronic disease, was asked. Questions were also asked about demographic and medical factors, and the medical chart was examined. Outcomes included glaucoma progression (yes, no) and visual field mean deviation. Logistic and linear regressions were used. A total of 180 patients were included (82 progressors and 98 nonprogressors). Although none of the 14 coping scales were associated with glaucoma progression ( P  > 0.05), higher denial was correlated with worse visual field mean deviation ( r  = −0.173, P  = 0.024). In a linear regression model including age, sex, education, depression, intraocular pressure, and family history of glaucoma, greater levels of denial (β = −1.37, 95% confidence interval [CI] −2.32, −0.41), Haitian ethnicity (β = −7.78, 95% CI −12.52, −3.04), and the number of glaucoma medications (β = −1.20, 95% CI −2.00, −0.38) were statistically significantly associated with visual field mean deviation. The maladaptive coping mechanism of denial was a risk factor for worse visual field mean deviation. Further prospective research will be required to verify the pathways by which denial may exert an effect on glaucomatous visual field loss.